2017
DOI: 10.1101/174979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DEET as a feeding deterrent

Abstract: The insect repellent N,N-diethyl-3-methylbenzamide (DEET), is a multimodal compound that acts as a spatial repellent as well as an irritant (contact repellent), thus being perceived by the insect’s olfactory and gustatory systems as an odorant and a tastant, respectively. Soon after DEET was developed, almost 6 decades ago, it was reported that it reduced mosquito feeding on blood mixed with this repellent. It is now known that the mosquito proboscis senses contact repellents with the tips (labella) of the lab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…In contrast, DEET completely inhibited blood feeding on contact (Figure 1K). These results support our conclusions from the arm-in-cage experiments in Figures 1E and 1F and agree with recent findings from Culex quinquefasciatus mosquitoes, which demonstrated that animals spent less time feeding on Parafilm-covered blood-soaked cotton balls if DEET was mixed into the blood [11]. These data support the hypothesis that DEET is bitter by ingestion, but its bitterness per se does not explain its highly effective contact chemorepellency.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, DEET completely inhibited blood feeding on contact (Figure 1K). These results support our conclusions from the arm-in-cage experiments in Figures 1E and 1F and agree with recent findings from Culex quinquefasciatus mosquitoes, which demonstrated that animals spent less time feeding on Parafilm-covered blood-soaked cotton balls if DEET was mixed into the blood [11]. These data support the hypothesis that DEET is bitter by ingestion, but its bitterness per se does not explain its highly effective contact chemorepellency.…”
Section: Resultssupporting
confidence: 92%
“…DEET (N, N-diethyl-meta-toluamide) is the most effective and widely used insect repellent, but its mechanism of action is both complex and controversial [1]. DEET acts on insect smell [2][3][4][5][6] and taste [7][8][9][10][11], and its olfactory mode of action requires the odorant coreceptor orco [2,3,6]. We previously observed that orco mutant female Aedes aegypti mosquitoes are strongly attracted to humans even in the presence of DEET, but they are rapidly repelled after contacting DEET-treated skin [6].…”
mentioning
confidence: 99%
“…1J). These results agree with recent findings from Culex quinquefasciatus mosquitoes, which demonstrated that animals spent less time feeding on Parafilm-covered blood-soaked cotton balls if DEET was mixed into the blood [11]. These data support the hypothesis that contact DEET repellency is independent of bitter taste, and that an unknown, sensory mechanism repels Ae.…”
Section: Deet and Bitter Compounds Are Repellent When Ingested But Osupporting
confidence: 92%
“…
DEET (N, N-diethyl-meta-toluamide) is the most effective and broadly used insect repellent, but its mechanism of action is both complex and controversial [1]. Previous work demonstrated that DEET acts both on insect smell [2][3][4][5][6] and taste [7][8][9][10][11] systems. Its olfactory mode of action requires the odorant co-receptor orco [2, 3, 6], while its gustatory repellency is mediated by activation of bitter taste receptors and neurons in the proboscis upon ingestion [8].
…”
mentioning
confidence: 99%
“…DEET has been reported to function as a feeding deterrent. 23,24,[42][43][44] Gr32a, Gr33a and Gr66a are widely expressed in bitter-sensing neurons, and are thought to be necessary for DEET repellence. 23 However, expression of these three gustatory receptors in sweet-sensing neurons failed to result in DEET sensitivity, implying that there are additional components remaining to be uncovered.…”
Section: Discussionmentioning
confidence: 99%